Metabolic profiling reveals key metabolites regulating adventitious root formation in ancient Platycladus orientalis cuttings - Chang, Ermei; Guo, Wei; Dong, Yao; Jia, Zirui; Zhao, Xiulian; Jiang, Zeping; Zhang, Li; Zhang, Jin; Liu, Jianfeng (Frontiers in Plant Science, 2023)
Platycladus orientalis, a common horticultural tree species, has an extremely long life span and forms a graceful canopy. Their branches, leaves and cones have been used in traditional Chinese medicine. However, difficulty in rooting is the main limiting factor for the conservation of germplasm resources. This study shows that the rooting rates and root numbers of cuttings were significantly reduced in ancient P. orientalis donors compared to 5-year-old P. orientalis donors. The contents of differentially accumulated metabolites (DAMs) in phenylpropanoid (caffeic acid, coniferyl-alcohol) and flavonoid biosynthesis (cinnamoyl-CoA, isoliquiritigenin) pathways increased significantly in cuttings propagated from ancient P. orientalis donors compared to 5-year-old P. orientalis donors during adventitious root (AR) formation. These DAMs may prevent the ancient P. orientalis cuttings from rooting, and gradual lignification of callus was one of the main reasons for the failed rooting of ancient P. orientalis cuttings. The rooting rates of ancient P. orientalis cuttings was improved by wounding the callus to identify wounding-induced rooting-promoting metabolites. After wounding, the contents of DAMs in zeatin (5'-Methylthioadenosine, cis-zeatin-O-glucoside, and adenine) and aminoacyl-tRNA biosynthesis (L-glutamine, L-histidine, L-isoleucine, L-leucine, and L-arginine) pathways increased might promote cell division and provided energy for the rooting process. The findings of our study suggest that breaking down the lignification of callus via wounding can eventually improve the rooting rates of ancient P. orientalis cuttings, which provides a new solution for cuttings of other difficult-to-root horticultural and woody plants.